1996
DOI: 10.1002/j.1460-2075.1996.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

The beta-amyloid domain is essential for axonal sorting of amyloid precursor protein.

Abstract: We have analysed the axonal sorting signals of amyloid precursor protein (APP). Wild‐type and mutant versions of human APP were expressed in hippocampal neurons using the Semliki forest virus system. We show that wild‐type APP and mutations implicated in Alzheimer's disease and another brain beta‐amyloidosis are sorted to the axon. By analysis of deletion mutants we found that the membrane‐inserted APP ectodomain but not the cytoplasmic tail is required for axonal sorting. Systematic deletions of the APP ectod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
102
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 52 publications
12
102
1
Order By: Relevance
“…We investigated whether cholesterol depletion would affect secretion of A␤40 and A␤42 in neurons. We expressed the human APP gene in primary rat hippocampal neurons by infection with SFV encoding the human APP (SFV-APP) (23,(30)(31)(32). Cholesterol was depleted from hippocampal neurons by two different strategies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated whether cholesterol depletion would affect secretion of A␤40 and A␤42 in neurons. We expressed the human APP gene in primary rat hippocampal neurons by infection with SFV encoding the human APP (SFV-APP) (23,(30)(31)(32). Cholesterol was depleted from hippocampal neurons by two different strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol is important for protein trafficking (44), and the A␤ domain in APP has been identified to be important for axonal transport of APP (32). Furthermore, A␤ is an apical targeted peptide in cholesterol-depleted MDCK cells (45).…”
Section: Discussionmentioning
confidence: 99%
“…Without ␤-cleavage, ␥-cleavage of Sp-C111 produces a 5.5-kDa A␤-like peptide consisting of the A␤-domain and the first 12 amino acids preceding the A␤-domain. In this regard C111 resembles more the C99 construct that does not require ␤-secretase cleavage for ␥-secretase activation (56). Thus, the relevant A␤ generating secretases may act here independent of each other.…”
Section: Methodsmentioning
confidence: 99%
“…The SpeI site in the 3Ј-untranslated region of the APP cDNA was removed by Klenow polymerase and the resultant blunt ends were re-ligated prior to cloning into the expression vector pSFV1 (56). This was necessary as the pSFV1/APP have to be linearized from the SpeI site of pSFV1.…”
Section: Methodsmentioning
confidence: 99%
“…Although APP, as a membrane receptor along with kinesin-1 microtubular motor protein, reaches an unprecedented fast and unidirectional axonal transportation, however, the exact nature of APP carriers into axons and dendrites is not fully recognized. Recently, it has been reported that the sorting signal of APP toward dendritic and axonal compartments seems to follow no specific pathways, 80 which implies the distinct behavior of neurons, compared to the other peripheral cells, for handling polarized trafficking of APP.…”
Section: ■ Intracellular Trafficking Of Appmentioning
confidence: 99%